2018
DOI: 10.1101/330969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathways of pathogenicity: The transcriptional stages of germination in the fatal fungal pathogen Rhizopus delemar

Abstract: word count: 197 16 Text word count: 4883 17 2 Abstract 18

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The necessity of genes involved in chitin synthesis and regulation appeared important for both R. delemar and R. microsporus in response to phagocytosis (Supplemental Figure S4). In previous work we also highlighted the importance of chitin synthase for germination (Sephton-Clark et al 2018). When fungal spores were pre-treated with the chitin synthesis inhibitor Nikkomycin Z (24 μg/ml), spores failed to germinate, displayed less chitin/chitosan in their outer cell wall (Supplemental Figure S5) and macrophage survival was increased at 7.5 hours post infection (Figure 8).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The necessity of genes involved in chitin synthesis and regulation appeared important for both R. delemar and R. microsporus in response to phagocytosis (Supplemental Figure S4). In previous work we also highlighted the importance of chitin synthase for germination (Sephton-Clark et al 2018). When fungal spores were pre-treated with the chitin synthesis inhibitor Nikkomycin Z (24 μg/ml), spores failed to germinate, displayed less chitin/chitosan in their outer cell wall (Supplemental Figure S5) and macrophage survival was increased at 7.5 hours post infection (Figure 8).…”
Section: Resultsmentioning
confidence: 75%
“…R. delemar exhibits rapid germination followed by hyphal extension (Sephton-Clark et al, 2018). The transcriptional profile we observe here in macrophages exposed to R. delemar is consistent with a strong damage response, likely prompted by the germination of R. delemar spores.…”
Section: Resultsmentioning
confidence: 99%
“…However, the routes of infection of pathogenic fungi remain unknown. Several studies have reported fungal spores dispersed in air are associated with pulmonary or disseminated infections [13], propagules present in soil and plant debris are related to cutaneous/subcutaneous mycosis in the warm-blooded host [14], and the hypothesis of infection via plants or by animals [15]. In addition, fungi colonize the skin, hair, and nails, which use keratin as a nutrient source [16].…”
Section: Introductionmentioning
confidence: 99%
“…S1) (Lau et al 2020; Xie et al 2020; Xie et al 2021) and Fusarium graminearum (Kim et al 2018), the representative species of the phyla Basidiomycota and Ascomycota, respectively, from sexual or asexual spore germination to vegetative growth and to sexual reproduction, were acquired and analysed. Additionally, the germination process of Rhizopus delemar (Sephton-Clark et al 2018), a Mucoromycota, was included in the examination. We aimed to (i) provide a more detailed developmental hourglass model in fungi; (ii) reveal the similarities and differences on gene expressions and functional features during the developmental process in fungal species, and across the kingdoms Animalia, Plantae, and Fungi.…”
mentioning
confidence: 99%